2018
DOI: 10.1111/cen.13856
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vitamin D status and its correlation with gonadal function in children at mini‐puberty

Abstract: A modest effect of 25(OH)D was identified on total testosterone and inhibin B in girls at mini-puberty. The 25(OH)D may have an effect on gonadal function during early life. Randomized controlled trials could clarify the importance of vitamin D on gonadal hormones at mini-puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Inhibin B has been proposed as a direct marker of Sertoli cell function and indirect marker of spermatogenesis (27,28) , and can be correlated with testis volume and testosterone production (29) , this was proved in this study by the significant positive correlation between serum inhibin B and testosterone levels. Reduction of inhibin B has been ascribed to an early arrest of spermatogenesis or a depletion of germ cells and associated with a reduced testicular volume (29) .…”
Section: Discussionsupporting
confidence: 55%
“…Inhibin B has been proposed as a direct marker of Sertoli cell function and indirect marker of spermatogenesis (27,28) , and can be correlated with testis volume and testosterone production (29) , this was proved in this study by the significant positive correlation between serum inhibin B and testosterone levels. Reduction of inhibin B has been ascribed to an early arrest of spermatogenesis or a depletion of germ cells and associated with a reduced testicular volume (29) .…”
Section: Discussionsupporting
confidence: 55%
“…Consequently, VDD decreases calcium absorption, exacerbating osteoporosis. Accordingly, the effects of VD supplementation observed in this trial may play a preventive role against osteoporosis during early life42 without any adverse effect on E2 levels. Therefore, the combination may be recommended for improving musculoskeletal outcome 43.…”
Section: Discussionmentioning
confidence: 74%
“…There is a lack of studies addressing the association of vitamin D deficiency with gonadal and sex hormones in children and adolescents in the pubertal stage. In the study of Kılınç et al (2019), which assessed the association between 25(OH)D levels and gonadal hormones in mini-puberty, which consists of transient activation of the hypothalamic-pituitary-gonadal (HPG) axis within the first few months of life in the healthy infants, they observed that the total testosterone levels were higher in girls with 25(OH)D deficiency than in girls with sufficient levels of vitamin D. On this matter, previous studies have suggested a stimulatory role of vitamin D on testosterone production (Blomberg Jensen 2012; Huang et al 2015;Lorenzen et al 2017). During adulthood, this hormone is produced by the testicular Leydig cells in response to LH stimulation.…”
Section: Discussionmentioning
confidence: 99%